STUDI FASIES FORMASI WUNGKAL-GAMPING JALUR GUNUNG GAJAH, DESA GUNUNG GAJAH, KECAMATAN BAYAT, KABUPATEN KLATEN, PROVINSI JAWA TENGAH - , YASINTA DEWI S ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Wungkal-Gamping formation is the oldest sedimentary rock which exposes in the Southern Mountains precisely in the area of Bayat. There is only geological information about this formation because the limited outcrop deployment. This study aims to determine facies rocks based on the stratigraphy measurements on this latest line as result of the excavation on Gunung Gajah village. In this research, stratigraphy measurements is done by jacob stick method to record the facies characteristic include geometry, lithology, sedimentary structures, and fossils in study area. The results are described in measured stratigraphy coloumn with 1:10 scale, the dividing of facies rocks, petrography and paleontology samples to determine the environment, age, mechanism and dynamics of sedimentation area of research. Research area is located at the 3 line in Gunung Gajah village precisely at coordinates 9141627 mU and 0464029 mT (North part) to 9141546 mU and 0463988 mT (South part). There are 9 facies in the section of research which are A, B, C, D, E, F, G, H, and I. These 9 facies are divided into 5 different facies associations, which are facies association 1 in proximal of slope-type fan delta, facies associations 2, 3, 4 and 5 in tidal flat. The age deposition begins in Early Eocene (P8) to Middle Eocene (P13). There is an erosional unconformity boundary between Early Eocene (P8) to Middle Eocene (P10). Mechanism of sedimentation on the lower part of Wungkal-Gamping formation is debris flow continued with suspension currents, and traction currents influenced by tides and waves of sea water. In general, the dynamics of sedimentation starts with the shallowing process at P8. Furthermore, it continued by the deeper process at P10 then shallowing process at P11. At early P12 due the deeper process then shallowing process until P13.